Life of Muslims in Germany, and Its Contextualisation to Indonesian Islam - Saputra, Rangga Eka (Studia Islamika, 2018)
A PPIMâ€™s junior researcher together with 13 young Indonesian Muslim intellectuals participated in Life of Muslims in Germany Program organized by Goethe Institut during 8-21 July 2018. This event explored Muslim everyday life in Germany through academic and cultural discussions in universities, research and cultural centres, and state officials. Therefore, this document is his insight to describe Muslim life in Germany and its contextualisation for Indonesian Muslim based on experiences in this program. This document article depicts two main issues which are happening in Germany: Muslim integration after the wave of refugees as a result of bloodiest conflict in Middle East and German governmentâ€™s policy in religious pluralism issues.This program had been initiated in order to bridge cultural understanding for Indonesia, as the most populous Muslim country in the world, toward Muslim life in Germany. Indonesia has been considered as a strategic country which stands for disseminating moderate Islam. In addition, Dr. Heinrich Blomeke, Goethe-Institut, Institute and Regional Director Southeast Asia/Australia/New Zealand, said â€œthe participants will engage in academic discussions and visit Muslim cultural organisation to obtain an insight about Muslim everyday life in German secular state. This program gives an opportunity for them and some Germanyâ€™s institutions to share their ideas regarding the experiences of Muslim life in Germany and Indonesiaâ€.Â